Comparative Efficiency Assessment of Primary Care Models Using Data Envelopment Analysis - Milliken, Olga; Devlin, Rose Anne; Barham, Vicky; Hogg, William; Dahrouge, Simone; Russell, Grant (Université d'Ottawa | University of Ottawa, 2008)
This paper compares the productive efficiencies of four models of primary care service delivery in Ontario, Canada, using the data envelopment analysis (DEA) method. Particular care is taken to include quality of service as part of our output measure. The influence of the delivery model on productive efficiency is disentangled from patient characteristics using regression analysis. Significant differences are found in the efficiency scores across models and within each model. In general, the fee-for-service arrangement ranks the highest and the community-health-centre model the lowest in efficiency scoring. The reliance of our input measures on costs and number of patients, clearly favours the fee-for-service model. Patient characteristics contribute little to explaining differences in the efficiency ranking across the models. / Cet article compare l’efficience productive dans quatre modèles de prestation de soins primaires en Ontario, au Canada, en utilisant la méthodologie du DEA (Data Envelopement Analysis). Une attention particulière a été portée sur l’inclusion la qualité du service de soin santé dans la mesure de l’extrant (output). L'influence du modèle de prestation sur l'efficience productive a été séparée des caractéristiques du patient en utilisant une analyse de régression. Des différences significatives ont été trouvées dans l'efficience entre modèles et à l’intérieur de chaque modèle. En général, les arrangements avec services-payants arrivent en tête, alors que les modèles de centre de santé communautaire performent le moins en termes d’efficience. Le recours au coût et au nombre de patients comme mesure de l’intrant est nettement favorable au modèle avec services-payants. Les caractéristiques du patient contribuent peu à expliquer les différences dans le classement de l'efficience entre les modèles.
Keywords: Productive Efficiency; DEA; Primary Health Care; Efficience Productive; DEA; Soins Primaires